Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities. Issue 8 (18th April 2022) - Chen, Ying-Ying; Hou, Jiang-Ping; Huang, Ling; Khan, Afsar; Xing, Fei-Fei; Zhang, Xiao-Han; Han, De-Feng; Yan, Shi-Li; Cao, Gui-Dong; Jiao, Qi-Yang; Liu, Dejie; Zhu, Xuwei; et al.
Abstract: A new diarylheptanoid, (1 R, 2 S, 3 S, 5 S )-2, 3-dihydroxy-3', 3''-dimethoxy-4'-de- O -methylcentrolobine (1 ) and a new bisabolane-type sesquiterpenoid, (1 R, 7 S )-1, 12, 13-trihydroxybisabola-3, 10-diene (2 ), together with nineteen known compounds (3 -21 ) were isolated from the EtOH extract of the stems and branches of Viscum coloratum (Kom.) Nakai. Their structures were elucidated by extensive analysis of 1 D and 2 D NMR spectra and from the HRESIMS. All the compounds were evaluated for their cytotoxic activity against eight human tumor cell lines. Graphical Abstract: